The investigation of health services in high schools in accordance with the views of principals, teachers and students (Elazig Province Sample) - Arabaci, I. Bakir (Turkish Education Assoc, 2010)
School is an organization where the most significant years of human life pass. High school term is a period which includes adolescence problems, as well. A sanitary and secure environment together with an affirmative culture of health provided in school brings about a healthy future. School health is becoming more of an issue in Turkey as in all advanced countries. In this study, the perceptions of administrators, teachers and students have been examined in respect of a healthy environment and culture in high schools. Descriptive scanning model has been utilized in this study. The data were obtained from 9 principals, 30 teachers and 302 students in 9 high school in Elazig Province and Baskil town. Results of this study reveal that a healthy environment has a positive effect on creating a healthy culture. Types and kinds of the schools, settlement and gender variables have been found to be significant as for participant's perceptions. Presence of a doctor, nurse and infirmary in schools affects positively participants' perceptions regarding to creating a healthy environment and culture.
Ortaö?retim okullannda sa?lik hizmetlerinin yönetici, ö?retmen ve ö?renci görü şlerine göre incelenmesi (elazi? ili örne?i)
Keywords: High school; school health services; healthy environment; culture of health